Antimicrobial activity and effects of Citral in species that cause oral diseases: literature review (Research, Society and Development, 2022)
Oral thrush is a common fungal infection in immunosuppressed patients. Studies demonstrate the activity of compounds from essential oils against involved microorganisms. This research carried out a literature review on the antimicrobial action of citral in species of interest to Dentistry. A search was carried out in the following databases: Pubmed, Science direct, Scielo, Lilacs and Cochrane. Articles from the last 15 years that investigated the antimicrobial and antifungal effect of citral in species of interest to Dentistry, as well as its mechanism of action and toxicity, were included. Eleven scientific articles were included for this review. Among the species studied, citral showed activity against Candida spp and bacteria such as Staphylococcus aureus, Streptoccocus mutans, Lactobacillus spp. Its mechanism of action has not been determined, and one of the studies reported low cytotoxicity. It is concluded that citral has antimicrobial and antifungal activity in species that cause oral diseases.